PENERAPAN MODEL PEMBELAJARAN INDUKTIF UNTUK MENINGKATKAN KETERAMPILAN MENGGAMBAR ILUSTRASI SISWA KELAS IV SD NEGERI 97 PEKANBARU - Fitri Asbeni; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the low ketermpilan students in drawing illustrations. Based on preliminary data from 30 students in the fourth grade, students who are skilled only 13 people and are quite skilled as many as 17 people with an average score of students in the classical style was 60.9. This has led researchers to apply inductive learning model in teaching art in drawing illustrations. Inductive learning is a process of give presentations to students about examples or illustrations, the topic that will be studied and then guide the students think that the learning objectives achieved. Therefore, action should be taken of teachers is to improve students' skills in drawing so that the classroom atmosphere to be comfortable and not boring for the students, using the approach to disclosure forms or images is simpler but does not eliminate the properties aesthetically a work of art. Based on the research results, when applied inductive learning model can improve drawing skills illustrations of fourth grade students of SDN 97 Pekanbaru on Arts and Culture Learning and Skills. Improvement occurring after the application of inductive learning model is the increased activity of the teacher, student activities, and skill-building drawing illustration studentsKeywords : Inductive learning model, students, Skills